Relation of growth-differentiation factor-15 levels and number of circulating endothelial progenitor cells in patients with type 2 diabetes mellitus - Kremzer, A. A.; Кремзер, Олександр Олександрович (publishing center of the ESCBM, The Czech Republic, 2018)
Background: risk stratification of patients with established type 2 diabetes mellitus (DM) is under scientific discussion and appears to be controversial issue. The objective: to investigate relationship between levels of growth differentiation factor-15 (GDF-15) and circulating number of endothelial progenitor cells (EPCs) with angiopoetic phenotypes: CD34+CD14+CD309+, and CD34+CD14+CD309+Tie2+ in patients with type 2 DM.
Keywords: тези доповідей; growth differentiation factor-15; endothelial progenitor cells; type 2 diabetes mellitus